Klasifikasi Opini Dengan Menggunakan Algoritma K-Nearest Neighbor Pada Berita Vaksinasi Di Twitter - Dede Sandi (FKOM UNIKU, 2022)
As technology develops so rapidly in collecting data, it results in a huge pile of data. Through the amount of data, so it becomes a necessity to take advantage of the data. The use of data is of course aimed at receiving crucial news from the data patterns formed. Data that can be used can be obtained from social media, one of which is Twitter. Twitter is a social media that has approximately 50 million users in Indonesia. With so many users in Indonesia, it can be utilized in the use of a lot of data as well. To get the data, one of the algorithms is K-Nearest Neighbor Classifier or KNN. The KNN work system is to calculate the closest distance from the test record to the test record using the test scenario method. The result of the KNN process is the shortest distance from the test record to the test record of K as needed.